Marine auxiliary machinery - McGeorge, H. D. (H. David) (Elsevier, 1995)
The seventh edition of this classic marine textbook is now available for the first time in paperback. This highly respected book instructs both students and sea-going engineers in the operation, care and maintenance of the auxiliary machinery and apparatus on board ship and is essential reading for marine engineers preparing for British Certificates of Competency examinations, US Licenses and similar qualifications elsewhere.